2020
DOI: 10.2298/pac2002102d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen vacancy defects and cobalt doping on optical, electronic and photocatalytic properties of ultrafine SnO2-δ nanocrystals

Abstract: Ultrafine pure and cobalt doped SnO2-? nanocrystals (Sn1-xCoxO2-?, 0 ? x ? 0.05) were synthesized by microwave-assisted hydrothermal method. The as-prepared nanocrystals have single phase tetragonal rutile structure. With increase of Co content (x > 0.01), Co entered into SnO2 lattice in mixed Co2+/Co3+ state. Pronounced blue shift of the band gap with cobalt doping originated from the combined effect of quantum confinement and Burnstain-Moss shift. Raman and photoluminescence study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It can be noticed that the Raman modes are broadened, which is due to NP low crystallinity . A typical set of modes for SnO 2 , according to the literature data, usually is a range of 450–670 cm –1 and it is characteristic for all the as-prepared samples. As for O 1s XPS peaks, the peak split procedure was also provided for Raman spectra in order to reveal the merged modes as described in Section .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noticed that the Raman modes are broadened, which is due to NP low crystallinity . A typical set of modes for SnO 2 , according to the literature data, usually is a range of 450–670 cm –1 and it is characteristic for all the as-prepared samples. As for O 1s XPS peaks, the peak split procedure was also provided for Raman spectra in order to reveal the merged modes as described in Section .…”
Section: Resultsmentioning
confidence: 99%
“…As for O 1s XPS peaks, the peak split procedure was also provided for Raman spectra in order to reveal the merged modes as described in Section . According to a previous study, the signal in the region 543–551 cm –1 is usually referred to as the silent mode B 1u , corresponding to vibrations between the Sn and O atoms. In regards to the peak around 623–628 cm –1 belongs to the A 1g mode, which also corresponds to symmetric Sn–O stretching .…”
Section: Resultsmentioning
confidence: 99%
“…[16] The cubic zirconia exhibits various colors through the doping of different transition metal elements, including Cr, Co, and Mn, which change the width of the bandgap, allowing it to absorb the energy of visible light and thus produce different light absorption. [17][18][19] Because of the different valence state between impurity elements and zirconia, some defects are usually generated in the lattice to balance the electric valence. Previous studies have demonstrated that the presence of defects may likewise affect the optical absorption of the crystal.…”
Section: Doi: 101002/pssb202300227mentioning
confidence: 99%
“…A photoluminescence technique was applied to verify the luminescence intensity of the doped and undoped SnO 2 samples. Their analysis suggests that the Co doping in the SnO 2 structure resulted in a decrease of the in-plane oxygen vacancies, leading to a drop in the efficiency of the photocatalyst for the methylene blue degradation [2]. The last two examples show that the doping of the material is not enough alone to achieve higher performance, rather, also important is the synthesis method.…”
Section: Sno 2 and D-sno 2 Photocatalysismentioning
confidence: 99%
“…The growth of fundamental and applied research on nanomaterials in several fields in the last three decades indicates the relevance of nanostructures and their potential applications. Among metal oxide semiconductors, tin dioxide (SnO 2 ) has been the subject of interest in numerous research projects due to its excellent physicochemical properties, such as high photosensitivity, chemical, thermal and mechanical stability, long-term stability, transparency, abundant reserve, low cost, and nontoxicity [1][2][3]. Tin dioxide is an n-type semiconductor with bandgap values between 3.6-3.8 eV; it has a low valence band potential, which gives the photogenerated holes in the valence band (VB) a high oxidation capacity [4].…”
Section: Introductionmentioning
confidence: 99%